ANALISIS KANDUNGAN KAFEIN PADA KOPI DI DESA SESAOT NARMADA MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Aryanu Fahmi Arwangga; Ida Ayu Raka Astiti Asih; I Wayan Sudiarta (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2016)
Coffee is one of the agriculture commodities that are cultivated by farmers. One of the compounds in the coffee is caffeine. Caffeine is one of alkaloids which contains in coffee bean. The purpose of this study was to determine the contents of caffeine in unripe coffee, pure coffee powder, and mix coffee powder by using UV-Vis spectrophotometer. Standard solutions of caffeine used were 1 ppm; 3 ppm; 6 ppm; 9 ppm; 12 ppm; and 15 ppm. Caffeine calibration curve equation was y = 0.0494x ??+ 0.01862 with a correlation coefficient (r) of 0.99714. Caffeine content in unripe coffee was 1,28±0,82 % with water content 3%, pure coffee powder 1,63±0,13 % with water content 1%, and mix coffee powder 0,87±0,01 % with water content 1%. According to SNI 01-7152-2006 maximum limit of caffeine in food and drink was 150 mg/day and 50 mg/dish.